Find all School-related info fast with the new School-Specific MBA Forum

 It is currently 03 May 2015, 15:36

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# If y = ( x^2 - y^2)/(x-y) where x not equal to y, then what

Author Message
TAGS:
Director
Joined: 11 Jun 2007
Posts: 649
Followers: 3

Kudos [?]: 82 [0], given: 0

If y = ( x^2 - y^2)/(x-y) where x not equal to y, then what [#permalink]  21 Nov 2007, 11:32
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 1 sessions
If y = ( x^2 - y^2)/(x-y) where x not equal to y, then what is the value of y ?

(1) x + y = 3
(2) x - y = 2
Director
Joined: 11 Jun 2007
Posts: 649
Followers: 3

Kudos [?]: 82 [0], given: 0

young_gun wrote:
A, y=3?

I chose A but OA is different.
CEO
Joined: 17 Nov 2007
Posts: 3578
Concentration: Entrepreneurship, Other
Schools: Chicago (Booth) - Class of 2011
GMAT 1: 750 Q50 V40
Followers: 406

Kudos [?]: 2140 [0], given: 359

Expert's post
D

y = ( x^2 - y^2)/(x-y)=(x+y)(x-y)/(x-y)=x+y ==> x=0; for any y.

1. x + y = 3 ==> y=3 suff
2. x - y = 2 ==> y=-2 suff
Current Student
Joined: 28 Dec 2004
Posts: 3391
Location: New York City
Schools: Wharton'11 HBS'12
Followers: 13

Kudos [?]: 181 [0], given: 2

I believe the OA is wrong then..

(x-y)(x+y)/(x-y)=y

y=x+y

x+y=3

y=3

sufficient
Director
Joined: 11 Jun 2007
Posts: 649
Followers: 3

Kudos [?]: 82 [0], given: 0

Can someone look at this problem? This is from GMATClub Challenges
http://gmatclub.com/tests/m/02/#q25

Also, is it possible for the variable y to have two different values for 2 cases?
Director
Joined: 08 Jun 2007
Posts: 584
Followers: 2

Kudos [?]: 79 [0], given: 0

eyunni wrote:
Can someone look at this problem? This is from GMATClub Challenges
http://gmatclub.com/tests/m/02/#q25

Also, is it possible for the variable y to have two different values for 2 cases?

yes it is possible that you may end up with different values for 2 cases.

In this case it should be D.

1) y = x + y = 3

2) y = x + y => x - y + y = 0 => y = -2
Manager
Joined: 03 Sep 2006
Posts: 233
Followers: 1

Kudos [?]: 5 [0], given: 0

Late, but D.
Agree with walker (same approach)
Similar topics Replies Last post
Similar
Topics:
4 If xy≠0 and x^2*y^2-xy=6, which of the following could be y 4 16 Jan 2012, 10:26
1 If xy ≠ 0 and x2y2 – xy = 6, which of the following could be 2 25 Feb 2011, 07:23
If xy ≠ 0 and x^2y^2 – xy = 6, which of the following could 3 09 Nov 2008, 19:47
If xy ≠ 0 and x^2y^2 xy = 6, which of the following 3 22 Aug 2006, 05:32
10 If xy not equal 0 and x^2*y^2 -xy = 6, which of the followin 6 18 Jan 2006, 19:15
Display posts from previous: Sort by